Controllability and hippocampal activation during pain expectation in fibromyalgia syndrome - Gonzalez Roldan, Ana Maria; Diesch, Eugen; Flor, Herta (Biological psychology, 2016)
To examine the role of perceived control in pain perception, fibromyalgia patients and healthy controls participated in a reaction time experiment under different conditions of pain controllability. No significant differences between groups were found in pain intensity and unpleasantness ratings. However, during the expectation of uncontrollable pain, patients compared to controls showed higher hippocampal activation. In addition, hippocampal activity during the pain expectation period predicted activation of the posterior cingulate cortex (PCC), precuneus and hippocampus during pain stimulation in fibromyalgia patients. The increased activation of the hippocampus during pain expectation and subsequent activation of the PCC/precuneus during the lack of control phase points towards an influence of pain perception through heightening of alertness and anxiety responses to pain in fibromyalgia patients.